2018
DOI: 10.1016/j.celrep.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Spatiotemporal Landscape of Neuromodulatory GPCR Signaling by Real-Time Imaging of cAMP in Intact Neurons and Circuits

Abstract: In the originally published version of this article, Figures 1G and 2B contained errors. In Figure 1G showing representative traces of cAMP responses, the graph of adenosine data was an inadvertent duplication of the dopamine data. In Figure 2B, the representative iMSN responses to dopamine in dendrites were an inadvertent duplication of the data from iMSN responses to dopamine in cell bodies. These figures have now been corrected online and appear below. These graphical errors do not change the data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…Consistently, we found that the activation of DMS-GPe iMSNs reduced ethanol-containing reward-seeking as much as the devalued state (10E10S presentation before the test) in the extinction tests. Recently developed CAMPER (cyclic adenosine monophosphate cAMP encoded reporter) strategy using different changes of cAMP level between G␣i-coupled A 1 R and G␣olfcoupled A 2A R may simultaneously determine the adenosine signaling-dependent dynamics of iMSNs and dMSNs in rewardseeking behaviors (Muntean et al, 2018). In the nucleus accumbens (NAc), however, it is not clear the distinction between dMSNs and iMSNs (Kupchik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that the activation of DMS-GPe iMSNs reduced ethanol-containing reward-seeking as much as the devalued state (10E10S presentation before the test) in the extinction tests. Recently developed CAMPER (cyclic adenosine monophosphate cAMP encoded reporter) strategy using different changes of cAMP level between G␣i-coupled A 1 R and G␣olfcoupled A 2A R may simultaneously determine the adenosine signaling-dependent dynamics of iMSNs and dMSNs in rewardseeking behaviors (Muntean et al, 2018). In the nucleus accumbens (NAc), however, it is not clear the distinction between dMSNs and iMSNs (Kupchik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many labs are addressing system bias issues and are beginning to evaluate signalling in more relevant cellular models, including primary neurons (Jamshidi et al, 2015;Ho et al, 2018;Ehrlich et al, 2019). A major limiting factor is the inability to evaluate signalling bias in vivo, although advances are ongoing, such as measuring cAMP signalling in mice (Muntean et al, 2018).…”
Section: G-protein Biased Kappa Opioid Receptor Agonistsmentioning
confidence: 99%
“…cAMPER and GCaMP6 reporter mice. We used the following Cre drivers to express fluorescent biosensors for calcium (GCaMP6s; Gt(ROSA)26Sor tm96(CAG-GCaMP6s)Hze ) [34]or cAMP (C57BL/6-Gt(ROSA)26Sor tm1(CAG-ECFP*/Rapgef3/Venus*)Kama /J) (cAMPER, The Jackson Laboratory, strain #032205) [35] directly and specifically in  cells (B6;129S4-Gcg em1(cre/ERT2)Khk /Mmjax) [36],  cells (B6.FVB(Cg)-Tg(Ucn3-cre)KF43Gsat/Mmucd) [37], or  cells (B6N.Cg-Sst tm2.1(cre)Zjh /J).…”
Section: Animalsmentioning
confidence: 99%